Teaching with hip hop in the 7-12 grade classroom a guide to supporting students' critical development through hip hop texts - Kelly, Lauren Leigh Ph.D (Eye on education, 2023)
This book presents ready-to-implement approaches for engaging with Hip Hop music and culture in the English classroom. As the most popular form of music and youth culture today, Hip Hop is a powerful medium through which students explore their identities and ground themselves in our modern world. Designed for novice and veteran English teachers, this book is filled with pedagogical tools, strategies, lesson plans, and real-world guidance on integrating Hip Hop into the curriculum. Through practical approaches and insights, Lauren Leigh Kelly invites teachers to use Hip Hop to support students' critical development and engagement with texts. Covering classroom practice, assessment strategies, and curricular and standards-based requirements, the lessons in this book will bolster students' language and critical thinking skills and help students to better understand the societal forces around them. The varied activities, assignments and handouts are designed to inspire teachers and easily permit them to modify the assignments to suit their own contexts. The impact of Hip Hop is undeniable, now more than ever; this is the perfect book for teachers who want to connect with their students, support meaning-making in the classroom, affirm the validity of youth culture, and foster an inclusive and engaging classroom environment